Needs Analysis of English for Specific Purposes (ESP) Materials for Beauty Students at Universitas Pendidikan Ganesha - Prabhasanti, Gusti Ayu Putu Ardia; Marsakawati, Ni Putu Era; Sari, Rima Andriani (Syntax Literate, 2024)
This study aims to identify the desired outcomes students seek after mastering English and determine the conducive learning environment and instructional materials that can enhance their motivation for language acquisition. A quantitative research method used in which the researchers administer a questionnaire to the participants. The questionnaire consisted of two categorizes namely, Learning Need Analysis (LNA) and Target Situation Analysis (TSA). 20 active participants from college students at five semester of Family Welfare Education (FEW) department at Universitas Pendidikan Ganesha involved in this research. The findings need to be considered to enhance the learning environment for students and provide tailored materials suited to their respective fields of study. This approach can also help increase their future careers, addressing any existing motivation deficits.